Microfluidic Bioprinting: Digitally Tunable Microfluidic Bioprinting of Multilayered Cannular Tissues (Adv. Mater. 43/2018). Issue 43 (22nd October 2018) - Pi, Qingmeng; Maharjan, Sushila; Yan, Xiang; Liu, Xiao; Singh, Bijay; van Genderen, Anne Metje; Robledo‐Padilla, Felipe; Parra‐Saldivar, Roberto; Hu, Ning; Jia, Weitao; Xu, Changliang; Kang, Jian; et al.
Abstract : In article number 1706913, Ali Khademhosseini, Yu Shrike Zhang, and co‐workers report a multichannel coaxial extrusion system for microfluidic bioprinting of circumferentially multilayered cannular tissues in a single step, which allows these perfusable cannular constructs to be tuned continuously between monolayers and multiple layers at regular intervals across the length of a bioprinted tube. This represents a fundamental step toward creating functional cannular tissues.